Phase-Shedding Control in Two Parallel Interleaved Three-Phase ZVS Inverters for Improved Light Load Efficiency - Rui Xie; Hongke Li; Bin Lin; Ouyang Xu; Xiaohe Wang; Yanguo Han; Jianliang Chen; Zhen Xin (IEEE Access, 2023)
The parallel interleaved three-phase inverters are suitable for high-power applications due to the current ripple canceling effect. The power density and efficiency can be further improved with the current ripple prediction (CRP) based high frequency zero-voltage switching (ZVS). However, the variable switching frequency increases rapidly as the power decrease, resulting in higher turn-off loss at light load despite the elimination of turn-on loss. In this paper, a phase-shedding control strategy is proposed along with the CRP based ZVS method to improve the light load efficiency. Only four phase-legs of the two parallel inverters operate at light load to reduce the switching frequency and the circulating current between the two clamping phase-legs. The proposed method can achieve full-range ZVS for all the switches without any auxiliary circuits or high frequency sensors. Current sharing can also be realized between the two clamping phase-legs based on accurate gate signal modulation. A 5 kW simulation and experimental prototype using SiC devices interfacing 400 V dc with three-phase 110 V ac grid is developed to verify the effectiveness of the proposed control strategy.